DOS MÉTODOS DE ALFABETIZAÇÃO ÀS PRÁTICAS DAS PROFESSORAS: um percurso a ser desvelado - Marreiros, Regina Sodré Almeida (2011)
This study presents the results of an exploratory research done in a municipal school in the city of São Luís, and it was proposed to investigate how teachers, who teach in classrooms of 1ºs years of fundamental teaching, have developed work of literacy in their classrooms. The purpose is to investigate issues about the process of literacy, specifically, the teaching of reading and writing for children of six and seven years. The focus of research was the analysis of learning conceptions of reading and writing and the relation between theory studied in the initial and continued formation with practice developed by teachers of literacy and how the literacy is evidenced in this practices. Were taken as reference four teachers, one coordinator man and one coordinator woman, with objective of to verify what is known and how is taught, thought and action. It is a qualitative research, with case study. For data collection were used interviews and semi-structured questionnaires, and observation of teaching practice. Data analysis indicated that teachers advocate a theoretical-constructivist base, considering child as active subject in the learning process. However, is evident also a fragmentation between theoretical and practical dimensions done by teachers in the process of construction of literacy.